Clinical and Epidemiological Aspects of Ankylosing Spondylitis Patients in a Single Center in Baghdad - Al Hafidh, Ali Hussein (Journal of Techniques, 2022)
Ankylosing spondylitis is a chronic inflammatory disease with axial involvement but also may present as a peripheral arthritis and extraarticular manifestations. Objective: To assess clinical aspects of ankylosing spondylitis patients and different associated demographic variables in Baghdad teaching hospital. Patients and methods: A cross-sectional study was carried out in Baghdad teaching hospital which includes 402 patients (≥ 18 years old) with a clinical diagnosis of AS according to Assessment of Spondylo Arthritis International Society for AS were involved in this study from June/2019 to June/2021. Demographic data and disease characteristics, presence of extra-articular manifestations (past and present) and measurement of disease activity was done by BASDAI, erythrocyte sedimentation rate (mm/h) and C-reactive protein (mg/L). In addition, HLAB27 typing was reported. Results: The age of onset for males was 24.87±8.8 and for females25.97±8.6 years, HLA typing HLA-B27 were 49.55% and 35.38% in males and females respectively and the association was found to be statistically significant (P. value =0.031). While family history was reported at 25.82% and 34.33% in males and females correspondingly. 75.07% of males compared to 71.38% of females were treated with Anti TNF therapy. Females had later onset of disease than males with lower percentage of HLA B27 positivity. Recommendation: more comprehensive assessment with advanced diagnostic and treatment standards.